PENERAPAN SENYUM PUSTAKAWAN SEBAGAI KETERAMPILAN SOSIAL DI PERPUSTAKAAN POLITEKNIK NEGERI PONTIANAK - Wahdini, Nur; Madeten, Sisilya Saman (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study discusses the Application of Smiling Librarians as a Social Skill in the Library of Politeknik Negeri Pontianak. The purpose of this study is to find out how the efforts of librarian politeknik Negeri Pontianak apply a smile to the visitors who visit the library to improve social skills. In this study, the authors retrieve data using qualitative and descriptive methods. Data collection is done by observation to field, interview and documentation to know clearly what happened in library. The results obtained in this study is the effort to apply smile librarian to users still not done optimally, looks stiff and unfriendly because rarely smile when serving users. Implementation of librarian smile should be done in all libraries to improve the quality and attractiveness of the librarian to the library. Librarian efforts in applying the librarian smile should be done optimally so that the perception of the librarian to a library to be better.Keyword : Smile, librarian, Library, Users, Skills